Microbial contamination of moose (Alces alces) and white-tailed deer (Odocoileus virginianus) carcasses harvested by hunters. (April 2019) - Sauvala, Mikaela; Laaksonen, Sauli; Laukkanen-Ninios, Riikka; Jalava, Katri; Stephan, Roger; Fredriksson-Ahomaa, Maria
Abstract: Hunting is currently a very popular activity, and interest in game meat is increasing. However, only limited research is available on the bacterial quality and safety of moose ( Alces alces ) and white-tailed deer ( Odocoileus virginianus ) harvested by hunters. Poor hunting hygiene can spread bacteria onto the carcasses, and inadequate chilling of the carcasses may increase the bacterial load on the carcass surface. We studied the bacterial contamination level on carcasses of 100 moose and 100 white-tailed deer shot in southern Finland. Hunters eviscerated carcasses in the field and skinned them in small slaughter facilities. During the sampling, same person visited 25 facilities located in 12 municipalities of four provinces. Moose carcasses had mean mesophilic aerobic bacteria (MAB), Enterobacteriaceae (EB) and Escherichia coli (EC) values of 4.2, 2.6 and 1.2 log10 cfu/cm 2, respectively, while deer carcass values were 4.5, 1.5 and 0.7 log10 cfu/cm 2, respectively. Moose carcasses were significantly more contaminated with EB and EC than deer carcasses. High bacterial counts (MAB>5.0 log10 cfu/cm 2 and EB > 2.5 log10 cfu/cm 2 ) on the carcasses were associated with the smallest facilities having only one room. The outdoor temperature and days between hunting and sampling affected the bacterial counts. High EB counts on the carcasses indicated a gut hit. Male gender was significantly more contaminated by EC and meat-borne pathogenic bacteria: Campylobacter spp., Salmonella spp., enteropathogenic Yersinia spp., stx- harbouring EC (STEC) and Listeria monocytogenes . STEC (28/200) and L. monocytogenes (20/200) were the most commonly detected bacteria by PCR. L. monocytogenes isolates of different sequence types (ST7, 18, 29, 37, 249, 412, 451 and 611) belonged to serotypes 1/2a (seven isolates) and 4b (three isolates). The virulence gene ail was detected in four Yersinia enterocolitica biotype 1A isolates and one Yersinia kristensenii isolate. The bacterial counts on the moose and deer carcasses varied highly, and more attention should be paid to hunting hygiene and training of hunters. Game meat may be a source of meat-borne pathogens, and close attention should therefore be paid when handling and preparing game. Highlights: A high proportion of the harvested moose and white-tailed deer carcasses were of low hygienic quality. High bacterial counts on the carcasses were associated with primitive facilities, outdoor temperature and gut hit. E. coli on the carcasses predicted the presence of pathogens. Campylobacter, Salmonella, Y. enterocolitica, STEC and L. monocytogenes, were detected on moose and deer carcasses.